Ejercicios de mecánica II - Ayala Martínez, Manuel; Flores Rodríguez, Angel F.; Mora Covarrubias, César P.; Navarro Alvarez, Miguel; Serrano Miranda, Hugo G.; Vargas López, Ricardo; Villegas Anaya, Manuel; Zurita Esquivel, Miguel M. (Facultad de Ingeniería, 1983)
EJERCICIOS DE MECANICA II
EJERCICIOS DE MECANICA II
Keywords: Apuntes; Ejercicios; Mecánica